Memórias de um olhar: algumas considerações psicanalíticas a partir da psicose - Urubatã, Marcella Hannah Nunes (2021)
This research returns to some memories in order to, from the interrogation about the moulds that build the image of the mad person, question what right the psychotic has to his subjectivity in the (hegemonic) treatments for his psychic suffering. Thus, we start from an altered focus: not aiming at the mad person, but going through his process against normality. Preserving the interest for the fractures produced by language in listening, looking, framing and in knowledge, this research starts from the field of Freudo-Lacanian psychoanalysis and the contribution of authors from other fields of knowledge. A text was built from some clippings in current News about the history of the Colônia Hospital (State of Minas Gerais - Brasil) and the researcher's memories, and it became clear the insistence on retracing the path of some words that, with the advent of modern subjectivity, turned into signs that shaped the assumption of a natural order for the human. During the development of the research, we presented a theoretical discussion towards the foundations of the clinical practice and the stories that, kept in oblivion, revealed the barbaric face of culture, the state of exception instituted by modern politics and the violence orchestrated by advanced capitalism in what is intended to set a care practice for mental suffering. The general problem with normality and the pathological runs through what is discussed from an encounter and what is being found throughout the research, leading us to the inversions produced by the inclusion of madness in the field of language. Accordingly, throughout the entire research, we work with the Freudian and Lacanian subversion of starting from psychosis to refer to the other structures and dissolve the boundary between the normal and the pathological; recognizing it as an important political act as it questions the environment to try to ensure not only the right to subjectivity in treatments for the psychotic's mental suffering.